Højere gaspriser kan føre til lavere boligpriser i dele af landet; Higher gas prices can lead to lower house prices in parts of Denmark - Marcus Mølbak Ingholt; Niels Framroze Møller (Danmarks Nationalbank, 2022)
– The price of natural gas has risen significantly since the summer of 2021. Higher heating costs may put downward pressure on homes heated with gas. Seen in isolation, the average price drop will be DKK 73,000 for a house with gas, if the gas price develops in line with the expectations of financial markets.
Keywords: 330; Housing finance; Inflation; wages and prices; Climate